2020
DOI: 10.1371/journal.pntd.0008155
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signatures of Plasmodium vivax infection during pregnancy and delivery outcomes

Abstract: Plasmodium vivax malaria is a neglected disease, particularly during pregnancy. Severe vivax malaria is associated with inflammatory responses but in pregnancy immune alterations make it uncertain as to what cytokine signatures predominate, and how the type and quantity of blood immune mediators influence delivery outcomes. We measured the plasma concentrations of a set of thirty-one biomarkers, comprising cytokines, chemokines and growth factors, in 987 plasma samples from a cohort of 572 pregnant women from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It is plausible that cytokines at delivery are already downregulated, which is in line with previous observations that showed inflammatory cytokines associated with episodes of P . vivax malaria during pregnancy that are lost at delivery [ 60 ]. Yet, a decrease in the plasma levels of IL-12 and C5a at delivery, particularly upon infections that occur during the first and third trimesters, was observed by us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that cytokines at delivery are already downregulated, which is in line with previous observations that showed inflammatory cytokines associated with episodes of P . vivax malaria during pregnancy that are lost at delivery [ 60 ]. Yet, a decrease in the plasma levels of IL-12 and C5a at delivery, particularly upon infections that occur during the first and third trimesters, was observed by us.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 has been previously associated with P . vivax infections during pregnancy [ 60 ], and C5a is considered a hypothetical key driver of PM pathogenesis, being associated with placental insufficiency and SGA babies, and correlated negatively and positively with ANG-1 and ANG-2, respectively [ 61 , 62 ]. Moreover, our study shows that both placental C5a and ANG-2 are diminished at delivery when women are infected for the first time during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of GM with TBS can range between 1.0% and 23.0% 9,36,41 and, with PCR, it rises to 49%. 24,28,47 MP with TBS has been reported in a range of 2% to 12%, which with PCR rises to 57%.…”
Section: Frequency Mapmentioning
confidence: 97%
“…A multicenter study with 572 pregnant women from 5 endemic countries for malaria (including Colombia), some with P. vivax infection and others without infection, indicates that in GM vivax the predominant immune response is Th1 and pro-inflammatory, when it is balanced with antiinflammatory cytokines can prevent negative outcomes during labor, while exacerbating the Th2 response may present deleterious effects during delivery. 36 Gnidehou's study in Colombia reported the presence of anti-VAR2CSA antibodies in pregnant women, men and children exposed to malaria, which inhibit the adhesion of infected erythrocytes to chondroitin sulfate A (CSA) in vitro. 37 However, a later study indicated that said IgG antibodies against VAR2CSA were not specific for plasmodial infection, highlighting that the specific antibodies are limited to the gestational period.…”
Section: Immunity In Mapmentioning
confidence: 99%
“…Likewise, higher concentrations of IL-10 were associated with complications in pregnant women with P . vivax malaria [ 21 ]. The identification of reliable biomarkers requires substantial evidence of their usefulness and efficiency under different epidemiological conditions before it can be generalized as a tool that supports the patient’s clinical management.…”
Section: Introductionmentioning
confidence: 99%